2019
DOI: 10.1002/mp.13717
|View full text |Cite
|
Sign up to set email alerts
|

MRI super‐resolution reconstruction for MRI‐guided adaptive radiotherapy using cascaded deep learning: In the presence of limited training data and unknown translation model

Abstract: Purpose Deep learning (DL)‐based super‐resolution (SR) reconstruction for magnetic resonance imaging (MRI) has recently been receiving attention due to the significant improvement in spatial resolution compared to conventional SR techniques. Challenges hindering the widespread implementation of these approaches remain, however. Low‐resolution (LR) MRIs captured in the clinic exhibit complex tissue structures obfuscated by noise that are difficult for a simple DL framework to handle. Moreover, training a robust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 48 publications
0
43
1
2
Order By: Relevance
“…SR images can be generated without transformation models since DL‐based methods utilize direct mapping based on information extracted from previous datasets. Recent studies have shown that the in‐plane resolution of physically scanned low‐spatial resolution 3D MRI can be improved to a four times higher resolution without compromising the image quality …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SR images can be generated without transformation models since DL‐based methods utilize direct mapping based on information extracted from previous datasets. Recent studies have shown that the in‐plane resolution of physically scanned low‐spatial resolution 3D MRI can be improved to a four times higher resolution without compromising the image quality …”
Section: Methodsmentioning
confidence: 99%
“…28,29 As post-processing means, they can generate images with high-SNR and high-spatial resolution within a reasonable processing time frame from low-SNR and low-spatial images obtained with high frame rates. 29 Utilizing super-resolution can overcome a spatial resolution limitation in 3D dynamic keyhole imaging. The aim of this paper is to propose high spatial and temporal resolution 3D MRIs in the presence of motion for real-time 3D MRgRT by combining 3D dynamic keyhole imaging with super-resolution generative (SRG) model.…”
Section: High-spatial High-temporal Keyhole Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Image SR, the idea of transforming low‐resolution into high‐resolution images and accurately recovering detail from sparse information, is perhaps a bit of a holy grail of image reconstruction, sounding like something straight out of science fiction, but it is in fact a field with a long history, albeit a more nascent history in Deep Learning. This technique is being applied in many other contexts, from improving the image quality of heart coronary MRAs, to adaptive MRI radiotherapy, to improving the appearance of multiple sclerosis white matter lesions on FLAIR images . However, unlike more generic methods like classical interpolation, the improved performance of many of these deep‐learning SR methods may be bound to a specific examination, protocol, or clinical application.…”
mentioning
confidence: 99%
“…This technique is being applied in many other contexts, from improving the image quality of heart coronary MRAs, to adaptive MRI radiotherapy, to improving the appearance of multiple sclerosis white matter lesions on FLAIR images. [3][4][5] However, unlike more generic methods like classical interpolation, the improved performance of many of these deep-learning SR methods may be bound to a specific examination, protocol, or clinical application. Because of the reduced model transparency of such deep-learning methods, continuous realworld evaluation is required, backed by prospective trials evaluating reconstruction from original low-resolution images at the scanner, to establish a safe and reliable evidence base for usage.…”
mentioning
confidence: 99%